SISTEM INFORMASI SIMPAN PINJAM KOPERASI PEGAWAI PADA SMK YUPPENTEK 1 TANGERANG - Abdul Hayat; Euis Sitinur Aisyah; Serly Ovtavia Ningrum (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2015)
Management of credit unions in SMK Yuppentek 1 Tangerang, still using the book and Microsoft Excel. This method is less effective for transactions occurring savings and loans so that the higher the count is also growing.besides activities of saving and borrowing data backup process is not automatically and inadequate storage placeso that the accumulation of papers.Given these problems, it needs to use cooperative savings andloan applications that can assist in the process of data processing and accounting of savings and loans. The research method used in this research literature, interviews, observation, analysis system, design system, and implementation system. The expected outcome of this research is with using database MySql.